Risk Factors of Hypertension Incidence at the Age of 20-45 Years - Sitti Marya Ulva; Endah Iriyanti (Universitas Mandala Waluya, 2021)
The incidence of hypertension in the Kulisusu Health Center Work Area, North Buton Regency is always included in the 10 biggest diseases, where in 2018 the number of sufferers was 216 people, in 2019 it rose to 344 people and in 2020 as many as 715 people. The purpose of this study was to determine the risk factors that influence the incidence of hypertension in the community at the age of 20-45 years in the Kulisusu Health Center Work Area, North Buton Regency. This type of research is analytic observation with case control design. The study population was 68 patients, with a sample of case is 40 respondents, which were taken by cluster random sampling. Descriptive and inferential data analysis using Chi-Square Test and Odds Ratio. The results showed that the risk factors for hypertension were family history (X2count=20.202; OR=9.333), income (X2count=6.146; OR=3.157), eating and drinking habits (X2count=33.885; OR=22.667), smoking habits (X2count=21.333; OR=11.667). The conclusion is that family history, income, eating and drinking habits and smoking habits are risk factors for hypertension in the Kulisusu Health Center Work Area. It is hoped that the public should avoid consuming foods that trigger hypertension, such as salty foods and containing saturated fat.